Philanthropy in a secular society - Benjamin Bittschi; Sarah Borgloh; Berthold U. Wigger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
In this study we investigate the relationship between religious and charitable giving. We test how income, the tax-price of giving and the German church tax, differently affect charitable donations of church members, individuals leaving church and nonchurch members. We find crowding in between the church tax and charitable giving for church members, but not for the church-leavers. In contrast to church members, donations of church-leavers and non-members are also highly responsive to the tax deductibility. Additionally, non-donors exhibit a significantly increased probability of leaving church compared to donors. Finally, we demonstrate that leaving church increases donations on the extensive margin but decrease giving along the intensive margin.
urn:nbn:de:bsz:180-madoc-408805
Keywords: H24; H41; Z12; 330; charitable giving; secularization; church tax; Germany; fixed-effects poisson model